2017
DOI: 10.3382/ps/pex079
|View full text |Cite
|
Sign up to set email alerts
|

Use of Bacillus Subtilis PB6 as a potential antibiotic growth promoter replacement in improving performance of broiler birds

Abstract: The intestinal gut health is one of the primary determinants of broiler growth and performance. Among the various enteric diseases, necrotic enteritis (NE) is an enterotoxemic disease caused by Clostridium perfringens, which can result in severe economic losses in poultry farming. Antibiotics like bacitracin methylene disalicylate (BMD) and avilamycin (AVL) are commonly used antibiotic growth promoters (AGP) in poultry feed to control necrotic enteritis in birds. Bacillus subtilis PB6 was reported to prevent n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 26 publications
6
43
0
Order By: Relevance
“…Bacillus subtilis (BAS) spores (Gram‐positive spore‐forming bacteria) are among the most used probiotics in poultry production due to their thermal stability during feed processing and their resistance to the physiological conditions of enteric ecosystem (Boroojeni, Svihus, Reichenbach, & Zentek, ; Li et al, ; Suva, Sureja, & Kheni, ). Positive effects of supplementing broiler diets with BAS strains have been reported in previous studies (Bai et al, ; Jayaraman, Das, Saini, Roy, & Chatterjee, ). These effects may be due to the ability of BAS in modulating the intestinal microbiota in favour of useful organisms, boosting the immune system, modification of the gut structure and morphology, and improving nutrients digestion and absorption (Elshaghabee, Rokana, Gulhane, Sharma, & Panwar, ; Jayaraman et al, ; Khochamit, Siripornadulsil, Sukon, & Siripornadulsil, ; Lee, Kim, Lillehoj, Jang, & Lee, ; Li et al, ).…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…Bacillus subtilis (BAS) spores (Gram‐positive spore‐forming bacteria) are among the most used probiotics in poultry production due to their thermal stability during feed processing and their resistance to the physiological conditions of enteric ecosystem (Boroojeni, Svihus, Reichenbach, & Zentek, ; Li et al, ; Suva, Sureja, & Kheni, ). Positive effects of supplementing broiler diets with BAS strains have been reported in previous studies (Bai et al, ; Jayaraman, Das, Saini, Roy, & Chatterjee, ). These effects may be due to the ability of BAS in modulating the intestinal microbiota in favour of useful organisms, boosting the immune system, modification of the gut structure and morphology, and improving nutrients digestion and absorption (Elshaghabee, Rokana, Gulhane, Sharma, & Panwar, ; Jayaraman et al, ; Khochamit, Siripornadulsil, Sukon, & Siripornadulsil, ; Lee, Kim, Lillehoj, Jang, & Lee, ; Li et al, ).…”
Section: Introductionsupporting
confidence: 60%
“…A review of literature reveals that the improvement in growth performance of birds fed diets supplemented with BAS may be associated with their ability in fine‐tuning gut ecosystem. This may happen through competitive adhesion and synthesis of the antimicrobial compound, immunomodulation, improving intestinal integrity and function, and secretion of digestive enzymes (Jayaraman et al, ; Lee et al, ; Li et al, ; Wang & Gu, ). In our study, histological and microbiology data also indicated that BAS led to improve intestinal mucosa morphology and maintained gut microbiota balance.…”
Section: Discussionmentioning
confidence: 99%
“…The use of probiotics in poultry diets has a direct role in modulating the composition of gut microbiota to promote the growth of beneficial species (11,(41)(42)(43). This study was part of a large project (40,44), that evaluated the efficacy of feeding Shaver White chickens with various levels of B. subtilis DSM 29784 (no probiotic [CON], 1.1Eϩ08 [LSSB], 2.2Eϩ08 [MSSB], or 1.1Eϩ09 [HSSB] CFU/kg of diet) in modulating the growth/ production performance and AR of nutrients across different phases of the growth/ production cycle.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of B. subtilis on growth performance improvements by alteration of intestinal microbiota in broilers is well documented (Abudabos, Alyemni, Dafalla, & Khan, ; Aliakbarpour et al., ; Jayaraman et al., ; Jeong & Kim, ; Sen et al., ; Wu et al., ). We also demonstrated that fermented products from B. subtilis could improve growth performance and intestinal morphology in broilers.…”
Section: Discussionmentioning
confidence: 99%
“…Among Bacillus species, Bacillus subtilis is the most commonly used probiotic microorganism in the animal feed industry (Cutting, 2011;Ghadban, 2002). It has been demonstrated that dietary supplementation of B. subtilis can modify intestinal microbiota and enhance growth performance in broilers (Aliakbarpour, Chamani, Rahimi, Sadeghi, & Qujeq, 2012;Jayaraman, Das, Saini, Roy, & Chatterjee, 2017;Jeong & Kim, 2014;Sen et al, 2012;Wu, Zhang, Guo, & Lin, 2011). Furthermore, dietary supplementation of B. subtilis spores in broilers is able to exclude gastrointestinal pathogens, including Escherichia coli and Salmonella spp.…”
mentioning
confidence: 99%